Genome Sequence of Clinical Acinetobacter baumannii Strain V15 - Permingeat, Valentin (2023)
Acinetobacter baumannii is recognized as a critical human pathogen by the World Health Organization, and therefore there is increasing interest in studying its biology and pathophysiology. Among other strains, A. baumannii V15 has been extensively used for these purposes. Here, the genome sequence of A. baumannii V15 is presented.